Light in the darkness : black holes, the universe, and us - Falcke, Heino, 1966-; Römer, Jörg, 1974- (HarperOne, an imprint of HarperCollinsPublishers, 2021)
"A fascinating and thought-provoking investigation into the nature of black holes-a blend of the spiritual, the philosophical, and the scientific-from the premier German astrophysicist who made history in 2019, capturing the first one on film"--